Defining the source region of the Indian Ocean Tsunami from GPS, altimeters, tide gauges and tsunami models - Pietrzak,J; Socquet,A; Ham,D; Simons,W; Vigny,C; Labeur,RJ; Schrama,E; Stelling,G; Vatvani,D (EARTH PLANET SC LETT, 2007)
To understand the role of the co-seismic moment magnitude, M-w, 9.1-9.3 Sumatra-Andaman Earthquake rupture mechanism on the severity of the Indian Ocean Tsunami, we used permanent Global Positioning System (GPS) data and carried out an analysis of co-seismic displacement and tsunami models. Tsunami modelling, validated against independent Jason-I altimetry data and tsunami arrival time data as determined from tide gauges, was used to analyse the results of five co-seismic slip inversions, using GPS, seismicity and/or uplift data. In this way we determined the most likely slip distribution characterized by slip maxima of similar to 20 m in the South and similar to 20 m in the North. We used both the distribution and temporal evolution of the co-seismic slip as derived from the GPS data. We show that the similar to 9 min propagation time of the rupture led to constructive interference of waves radiating first from the South and minutes later from the North, strengthening the tsunami in Southern India, Sri Lanka and Thailand. We conclude that the incorporation of permanent real-time GPS stations would represent a valuable component of future tsunami warning systems. (C) 2007 Elsevier B.V All rights reserved.